2002
DOI: 10.1375/bech.19.4.191
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Enhanced Group Triple P — Positive Parenting Program for Parents of Children with Attention-deficit/Hyperactivity Disorder

Abstract: The aim of this randomised controlled trial was to examine the efficacy of an Attention-deficit/ hyperactivity Disorder (ADHD)-specific, Enhanced (Level 5) Group Triple P intervention. Twenty families with a child with clinically diagnosed ADHD aged between 5 and 9 years participated. Families were randomly assigned to either an enhanced intervention group (Enhanced Group Triple P; EGTP) or a wait list (WL) condition. Using parent reports of child behaviour, parenting practices and family functioning in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 50 publications
(49 reference statements)
5
67
1
7
Order By: Relevance
“…All eleven [13][14][15][16][17][18][19][20][21][22][23] studies had a child ADHD symptom outcome (assessed using clinical interview or validated parental reported questionnaire). The overall standardized mean difference in the analysis for ADHD symptoms was significant and moderate (SMD = 0.68; 95%…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All eleven [13][14][15][16][17][18][19][20][21][22][23] studies had a child ADHD symptom outcome (assessed using clinical interview or validated parental reported questionnaire). The overall standardized mean difference in the analysis for ADHD symptoms was significant and moderate (SMD = 0.68; 95%…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity was also significant (χ 2 =46.79; l 2 =79%; p<0.001) (see Figure A). A sensitivity analysis which removed the five studies 13,16,18,22,23 that had allowed medication not only demonstrated that these findings were independent of medication status but that the strength of the association increased (SMD = 0.77; 95% CI 0. Heterogeneity was not significant (see Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The location was unclear in the remaining studies. Psychologists were in the majority as the self-care support agent but they accounted for less than half (14/33) of the interventions; 48,69,73,83,84,91,101,102,118,119,[163][164][165]168,171,174 a range of specific (e.g. teachers and counsellors 39,90,93,110,113,136,170 ) and non-specific (e.g.…”
Section: Analysis Of the Qualitative Perceptions Datamentioning
confidence: 99%
“…Several meta-analyses document the effectiveness of parenting programs across a range of parental and child outcomes (Barlow et al 2002;Kaminski et al 2008;Lundahl et al 2006;Serketich and Dumas 1996) such as autism (McConachie and Diggle 2007), developmental disabilities (Plant and Sanders 2007), anxiety disorders (Cartwright-Hatton et al 2011), feeding and sleeping problems (Turner et al 1994;Werle et al 1993), drug and alcohol problems (Battistich et al 2000), anti-social behavior (Scott et al 2001), attention deficit hyperactivity disorder (Hoath and Sanders 2002) and recurrent pain syndromes . Parenting programs have also been shown to improve couple interaction quality (Cowan et al 2011), parenting competence and stress (Gross et al 2003;Nixon et al 2003) and maternal depression (Sanders and McFarland 2000).…”
Section: Definition Of Parenting Programsmentioning
confidence: 99%